Business Marketing Strategies of Tour and Travel Agency to Survive in The Covid-19 Pandemic - Gagih Pradini; Anisa Putri Kusumaningrum; Fitri Agustiani; Indah Triwulan Dari (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
In early 2020, the world was shocked by the case of the spread of the Covid-19 outbreak which is increasingly widespread, but this has an impact on tourism activities. In Indonesia, one of the tourism sectors that feel the impact is the business of a travel agency or travel agent. In order to stay afloat in this pamdemi, of course, travel agents need a marketing strategy to sell their products. This research aims to find out what marketing strategies are used by travel agency businesses or travel agents to stay afloat in the Covid-19 pandemic with a case study of PT. Patih Indo Permai Tour and Travel. The method used is qualitative-descriptive using data triangulation consisting of, interviews to the Company, Customes, and Stakeholders (Tenants) at PT. Patih Indo Permai Tour and Travel. The results of this study are known to PT. Patih Indo Permai Tour and Travel affected by Covid-19, PT. Patih Indo Permai Tour and Travel conducts a Market Diverensification Marketing Depreciation Strategy, which sells products that are different from the previous products (providing SWAB Antigen / PCR Test services, renting out some office space, and opening cooperatives). The strategy was successfully carried out to meet the needs of the office and stabilize the company's revenue.